2009
DOI: 10.1182/asheducation-2009.1.497
|View full text |Cite
|
Sign up to set email alerts
|

Standard therapy of advanced Hodgkin lymphoma

Abstract: ABVD (doxorubicin, bleomycin, vinblastine and dacarbazine) continues to be the standard of care for patients with advanced-stage Hodgkin lymphoma (HL). Consolidation of primary chemotherapy with radiation or autologous stem cell transplantation (ASCT) has not demonstrated an improvement in overall survival in randomized controlled trials. Regimens such as escalated BEACOPP have more acute and late toxicities and survival benefits have yet to be confirmed.Despite effective therapy, ultimately 30% to 40% of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
1
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 67 publications
0
42
1
6
Order By: Relevance
“…However, 2-5% and 5-10% of patients have a primary refractory disease, and 10-15% and 25-30% of patients experience relapse after conventional chemotherapy in early-stage HL and advanced-stage HL, respectively [1,2]. For these patients, several studies have demonstrated that autologous hematopoietic stem cell transplantation (HSCT) can prolong survival [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…However, 2-5% and 5-10% of patients have a primary refractory disease, and 10-15% and 25-30% of patients experience relapse after conventional chemotherapy in early-stage HL and advanced-stage HL, respectively [1,2]. For these patients, several studies have demonstrated that autologous hematopoietic stem cell transplantation (HSCT) can prolong survival [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…6 In approximately 85% of patients chemotherapy and autologous bone marrow transplantation result in long-lasting remissions or cure but about 15% of patients still succumb to multiple relapses or have primary resistant disease. 7 Genomic instability is a hallmark of tumor cells. 8 Different pathways lead to such instability, but, in the context of HL, telomere dysfunction is a prime mechanism leading to the transition of H to RS cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients with advanced stage disease continue to have suboptimal outcomes, with 5-year freedom from progression rates of 47%-79% and relapse rates of 30%-40% [4,5]. Moreover, an additional 10%-15% of patients fail to enter remission with frontline therapy (primary refractory disease).…”
Section: Introductionmentioning
confidence: 99%